2011
DOI: 10.1103/physrevlett.107.268501
|View full text |Cite
|
Sign up to set email alerts
|

Possible Explanation of the Atmospheric Kinetic and Potential Energy Spectra

Abstract: We hypothesize that the observed wave number spectra of kinetic and potential energy in the atmosphere can be explained by assuming that there are two related cascade processes emanating from the same large-scale energy source, a downscale cascade of potential enstrophy, giving rise to the k(-3) spectrum at synoptic scales and a downscale energy cascade giving rise to the k(-5/3) spectrum at mesoscales. The amount of energy which is going into the downscale energy cascade is determined by the rate of system ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
52
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(60 citation statements)
references
References 29 publications
7
52
1
Order By: Relevance
“…In three dimensions (3D), energy is transferred in a direct cascade towards small scales [1,2], whereas in two dimensions (2D) energy undergoes an inverse cascade towards large scales [3,4]. Numerical simulations have confirmed this picture in both 3D [5] and 2D turbulence [6,7] but they have also shown that the two processes are not mutually exclusive and the coexistence of both a downscale and upscale energy transfer has been observed [8][9][10][11][12].…”
Section: Introductionsupporting
confidence: 55%
“…In three dimensions (3D), energy is transferred in a direct cascade towards small scales [1,2], whereas in two dimensions (2D) energy undergoes an inverse cascade towards large scales [3,4]. Numerical simulations have confirmed this picture in both 3D [5] and 2D turbulence [6,7] but they have also shown that the two processes are not mutually exclusive and the coexistence of both a downscale and upscale energy transfer has been observed [8][9][10][11][12].…”
Section: Introductionsupporting
confidence: 55%
“…h to a k −5/3 h spectrum have been simulated both in idealized numerical simulations (Kitamura & Matsuda 2006;Bartello 2010;Vallgren, Deusebio & Lindborg 2011) and atmospheric models (Skamarock 2004;Takahashi, Hamilton & Ohfuchi 2006;Hamilton, Takahashi & Ohfuchi 2008;Waite & Snyder 2009). Bartello (2010) simulated a strongly stratified and rotating flows in a triply periodic domain forced only at large scales.…”
Section: Introductionmentioning
confidence: 99%
“…In the first, which we call Q-forcing, the forcing is restricted to the q-equation. This is the same scheme as used in Vallgren et al (2011) and Deusebio et al (2013). In the second scheme, which we call mixed forcing or M-forcing, the forcing is applied to all three equations, with about twothirds of the energy injection into the ageostrophic modes, a 1 and a 2 .…”
Section: Simulationsmentioning
confidence: 99%
“…It has also been demonstrated that the strongly stratified turbulence regime can be obtained in the presence of system rotation (Lindborg 2005;Waite & Bartello 2006), provided that the rotation is not too strong. Recently, Vallgren, Deusebio & Lindborg (2011) and Deusebio, Vallgren & Lindborg (2013) carried out numerical simulations of strongly stratified turbulence at strong system rotation, that is at small Rossby number Ro = U/f L, where f is the Coriolis parameter. They showed that even for very small Ro a substantial part of the injected energy cascades towards small scales.…”
Section: Introductionmentioning
confidence: 99%